1997
DOI: 10.1111/j.1365-2621.1997.tb04446.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Physical and Sensory Attributes of Noodles with Added Sweetpotato and Soy Flour

Abstract: Noodles were prepared with sweetpotato flour or puree and defatted soy flour (DSF) added to all-purpose wheat flour. These ingredients provided ␤-carotene for vitamin A and protein. Test samples were compared with control noodles. Combinations of sweetpotato and DSF increased protein, ash and total dietary fiber and decreased fat and carbohydrates. Sweetpotato contributed orange color and ␤-carotene, while DSF reduced lightness and added no ␤-carotene. Both ingredients increased cooking loss-10.4% from sweetpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 5 publications
5
45
0
1
Order By: Relevance
“…Cooking loss increased to 11.2-15.8 g/100 g and 11.5-16.6 g/100 g as the levels of DSF and SPC increased to 15-45 g/100 g, respectively (Table 5). However, there was no significant difference of losses among the levels of DSF and SPC at 15 g/100 g and 30 g/100 g. Collins and Pangloli (1997) reported that addition of 10-15 g/100 g sweetpotato and soy flour in wheat noodles increased cooking loss of products. Cooking yield significantly increased as the levels of soy proteins increased; however, no significant difference of cooking yields among levels of DSF and SPC was observed (Table 4).…”
Section: Cooking Loss Of Pastamentioning
confidence: 92%
See 1 more Smart Citation
“…Cooking loss increased to 11.2-15.8 g/100 g and 11.5-16.6 g/100 g as the levels of DSF and SPC increased to 15-45 g/100 g, respectively (Table 5). However, there was no significant difference of losses among the levels of DSF and SPC at 15 g/100 g and 30 g/100 g. Collins and Pangloli (1997) reported that addition of 10-15 g/100 g sweetpotato and soy flour in wheat noodles increased cooking loss of products. Cooking yield significantly increased as the levels of soy proteins increased; however, no significant difference of cooking yields among levels of DSF and SPC was observed (Table 4).…”
Section: Cooking Loss Of Pastamentioning
confidence: 92%
“…It is considered as a staple and co-staple in many Asian and African countries (Woolfe, 1992). Sweetpotato flour has been added in pasta formulation but just used as a minor ingredient (Collado & Corke, 1996;Collins & Pangloli, 1997;Thirumaran & Ravindran, 1992). In wheat pasta, gluten protein contributes the desirable cooking qualities and texture of products (Feillet & Dexter, 1996).…”
Section: Introductionmentioning
confidence: 98%
“…Purple yams also can reduce plasma and hepatic cholesterol levels by feeding a 50% yam diet to mice (Chen, Wang, Cheng, & Wang, 2003). There is a new tendency to add vegetable materials to the basic ingredients of wheat flour (Collins & Pangloli, 1997;Senthil, Ravi, Bhat, & Seethalakshmi, 2002;Skrbic, Milovac, Dodig, & Filipcev, 2009;Wang, Rosell, & Benedito de Barber, 2002). Such added ingredients can provide different flavors, colors, additional nutrients and, often, health benefits.…”
Section: Introductionmentioning
confidence: 95%
“…Physicochemical properties of basic ingredients will be changed, in part, by the addition of these materials. Noodles that are prepared with sweet-potato flour and soy flour can increase the β-carotene and protein content as well as increase the cooking loss of noodles (Collins & Pangloli, 1997). The addition of barley flour can fortify the β-glucan content but decrease the volume and crumb elasticity of bread; nevertheless, this does not have negative effects on the overall acceptability of the resulting breads (Skrbic et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Pasta can be formulated according to the consumer's demand (Feillet et al 1996). Bahnassey and Khan (1986) and Collins and Pangloli (1997) used legumes flours to increase the nutritive value of pasta products. Results indicated a significant increase in protein and mineral content of pasta.…”
mentioning
confidence: 99%